Analysis of process parameters on spatter and dross in plasma arc cutting - Azlan, Ira Fatin; Ismail, Mohd Idris Shah; Samin, Razali (ModTech Publishing House, 2024)
Plasma arc cutting (PAC) process has advantages such as the ability to cut all electrically conductive materials and to cut various steel materials with medium and large thicknesses. It is also used in the cutting of high-strength structural steel with lower heat input and has a high cutting speed compared to the conventional machining process. In this present work, the spatter and dross formation on S275JR mild carbon steel with a thickness of 5 mm by plasma arc cutting were experimentally investigated. Cutting speed (1000 - 1500 min/min), arc current (90 - 110 A), and stand-off distance (2.5 – 4.5 mm) were selected as cutting parameters with three levels for each parameter. The gas pressure and nozzle diameter were kept constant at 6 bar and 1.5 mm, respectively. Following the completion of the PAC process, the observation and measurement of the spatter and dross were conducted using a digital microscope. The results showed that spatter formation was more prominent near the cut edge or kerf, especially when using a higher stand-off distance. As for the dross formation, the results show maximum length is 1.741 mm and the minimum height is 1.192 mm. Analysis of variance (ANOVA) method is employed to statistically analyse the results and shows the cutting speed and SOD are the most statistically significant. For minimizing dross formation, low arc current, higher levels of cutting speed and stand-off distance should be utilized.